Pengaruh Kompetensi Aparat Desa dan Pemanfaatan Teknologi Informasi Terhadap Akuntabilitas Pengelolaan Dana Desa: Studi Kasus di Kecamatan Tilango Kabupaten Gorontalo - Nurain Huda; Harun Blongkod; Ayu Rakhma Wuryandini (Masyarakat Ekonomi Syariah Bogor, 2024)
This study aims to investigate the influence of village apparatus competence and information techonology utilization on the accountability of village fund management in Tilango Sub-district, Gorontalo Regency. The study employed a quantitative method with primary data collected through a questionnaire. A pusposive sampling tecnique was employed, resulting in a sample size of 103 participants. The analysis method utilized is Sturctural Equation Modeling (SEM) with the assistance of AMOS software. The finding indicate that: 1) Village apparatus competence has an insignificant influence on the accountability of village fund management; 2) Information technology utilization also has an insignificant influence on the accountability of village fund management; 3) Both village apparatus competence and information technology utilization collectively have a significant influence on the accountability of village fund management.